A cross-sectional study of Canadian children's valuation of literacies across social contexts - Emily Bremer; Philip Jefferies; John Cairney; Dean Kriellaars (Frontiers Media S.A., 2023)
BackgroundChildren, on average, do not engage in sufficient physical activity to reap the physical, mental, and social health benefits. Understanding the value that children place on movement across social contexts, and the relative ranking of this valuation, may help us to understand and intervene on activity levels.MethodThis exploratory study examined the valuation of reading/writing, math, and movement across three social contexts (school, home, with friends) among children 6-13 years of age (N = 7,845; 51.3% male). Subjective task values across contexts were assessed with the valuing literacies subscale of the PLAYself. One-way Kruskal-Wallis ANOVAs were performed to test for differences between contexts and between literacies, respectively.ResultsSex differences and age-related variation were explored. Valuations of reading/writing (d = 1.16) and math (d = 1.33) decreased across context (school > family > friend), while the valuation of movement was relatively stable (d = 0.26). Valuations differed substantially with friends (p < 0.001, d = 1.03). Sex dependent effect sizes were minimal (d = 0.05-0.11).ConclusionsMovement is highly valued by children across social contexts; thus, programming across contexts should be prioritized to align with their valuation.